Effectiveness of immunobloting method in syphilis differential diagnostics in pregnancy - M. V. Serduckaya; A. M. Ivanov; A. B. Krivoruchko; D. V. Zaslavskiy; E. V. Hodosevich; F. A. Ovsannikov (Журнал инфектологии)
168 pregnant women suspected to be infected with syphilis were observed within this research. To prove the presence of antibody in whey blood to antigenes Treponema pallidum we used sets recomBlot Treponema IgM and recomBlot Treponema IgG («Microgen», Germany). In immunological observations the following indexes were included defining number of lymphocyte subpopulations (CD3+ -, CD4+ -, CD8+ -, CD16+ – , CD19+ и CD25+ – lymphocyte) and level in blood serum Interleukin-1β, Interleukin-2, Interleukin-4, Interleukin-8 и INF-γ. Treponema tests in 100% of cases showed positive results, regardless of patients’ category. An examination of pregnant women with serum resistance the immunobloting sensitivity for detecting IgG-antibodies was 61,6%. In 38,4% of cases bloting showed uncertain results, because it detected antibodies to only one or two out of 5 treponemnyh antigens. Level of INF-γ for pregnant women with serum resistance increases, this reflects predominance of immune regulation of Th-1 type. Based on the results we offer general scheme of dealing with pregnant patients with suspected syphilis. These results can be used for differential diagnosis of latent syphilis, and serum resistance.